Characteristics of selected concrete with tunnel excavation material. (30th December 2015) - Voit, K.; Zimmermann, T.
Highlights: The research investigates the mechanically characteristics of concrete using tunnel excavation materials. Determination of characteristics of concrete by using different cement types. The research incorporates experimental testing like compressive tests, bending tests and wedge splitting tests. The results provide basic as well as fracture mechanical parameters of concrete. Abstract: Infrastructure tunnels are an important element in transportation. In the process of tunnel driving, a large amount of excavating material accumulates. Strategies to reuse this material have been growing in popularity during recent years as a result of economic and environmental considerations. It is therefore necessary to reassess the material management concept and identify possibilities to recycle the excavated rock material at the same time. The aim of the current paper is to investigate the mechanically relevant parameters of concrete using various tunnel excavation materials as aggregates and different cement types (e.g. composite cements) by experimental testing. Thereby, basic material parameters of freshly mixed as well as hardened concrete and fracture relevant quantities of hardened concrete are determined. Moreover, the properties of plain concrete and fibre reinforced concrete with aggregates of tunnel excavation material are compared with each other.